IMPLEMENTATION OF MINISTER OF HEALTH REGULATION NO. 24 OF 2022 ON MENTAL HEALTH MEDICAL RECORDS AT MADANI HOSPITAL, PALU - Reza, Andi; Basofi Usman, Imam; Bahri, Syamsul (Berajah Journal, 2024)
Medical records are a critical component in determining the quality of healthcare services provided by hospitals. Comprehensive and accurate medical records serve multiple purposes, including administrative, legal, financial, research, educational, and documentation needs. This study aims to evaluate the implementation of the Minister of Health Regulation No. 24 of 2022 concerning mental health medical records at Madani Hospital, Palu. Using a qualitative approach, data were collected through interviews with five informants, including the Head of the Medical Records Unit, and document analysis. The research was conducted between May 15 and July 2, 2024. The findings reveal that while Madani Hospital has implemented the regulation, challenges persist, particularly regarding incomplete patient records caused by non-compliance among healthcare workers and limited human resources in the medical records unit. Moreover, the hospital relies on a hybrid system combining manual and electronic records due to insufficient infrastructure and funding. These challenges impact the efficiency and accuracy of record management. This study recommends regular supervision and training for medical records staff to ensure timely and accurate documentation. Strengthening human resources and transitioning to a fully electronic system are essential for enhancing compliance with the regulation and improving overall service quality.